2017
DOI: 10.1038/s41598-017-03397-2
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β peptides overexpression in retinal pigment epithelial cells via AAV-mediated gene transfer mimics AMD-like pathology in mice

Abstract: Age-related macular degeneration (AMD) is a progressive retinal neurodegenerative disorder characterized by extracellular deposits known as drusen. A major constituent of drusen deposits are Alzheimer disease-associated amyloid β (Aβ) peptides. To understand the etiology of Aβ proteostasis in AMD, we delivered recombinant adeno-associated virus (AAV) encoding Aβ42 and Aβ40 peptides fused to BRI2 protein by intraocular injection in C57BL/6J mice. Endogenous protease cleavage of such constructs leads to producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
1
23
1
Order By: Relevance
“…The number of drusen-like sub-retinal deposits were counted in a masked fashion from hematoxylin-eosin images of 12 month old Cryba1 f l/fl , vehicle-treated Cryba1 cKO and AKT2 inhibitor-treated Cryba1 cKO mice retinae respectively. Quantification of drusen-like sub-retinal deposits were done from these images by using the ImageJ/NIH image analysis system in a masked fashion 75 .…”
Section: Methodsmentioning
confidence: 99%
“…The number of drusen-like sub-retinal deposits were counted in a masked fashion from hematoxylin-eosin images of 12 month old Cryba1 f l/fl , vehicle-treated Cryba1 cKO and AKT2 inhibitor-treated Cryba1 cKO mice retinae respectively. Quantification of drusen-like sub-retinal deposits were done from these images by using the ImageJ/NIH image analysis system in a masked fashion 75 .…”
Section: Methodsmentioning
confidence: 99%
“…A potential relationship between Aβ-derived neurotoxins and retinal degeneration has been implicated in diabetes as well as aging and Alzheimer’s disease [ 21 ]. Aβ is found within RPE cells and in extracellular drusen deposits present between the RPE and Bruch’s membrane [ 22 , 23 ]. The accumulation of Aβ peptide in retina is responsible for the development of retinal cell apoptosis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed both tau and Aβ pathologies in the retina of 14 m Tg2576 mice (Liu et al, 2009; Hart et al, 2016) and APP immunoreactivity in the retina in a number of AD animal models, including Tg mouse models (hTgAPP tg/tg , APP SWE /PS1 ΔE9 , and APP SWE /PS1 M146L/L286V ) that exhibit several features of AD (Frederikse and Ren, 2002; Ning et al, 2008; Dutescu et al, 2009; Zhao et al, 2013; Du et al, 2015). Moreover, several studies found Aβ deposition in the drusen or retinal layers in AMD animal models (Crabb et al, 2002; Prasad et al, 2017). Anti-Aβ immunotherapy was reported to reduce ocular Aβ deposits in a mouse model of AMD (Ding et al, 2011).…”
Section: Resultsmentioning
confidence: 99%